Social Representation of Indigenous People in Curricula of Colombia, Ecuador, and Chile - Valderrama-Aguayo, Iván (2024)
Introduction. One of the main tensions faced by modern educational systems is their ability to train critical citizens without losing sight of their specific cultural origins. Objective. This study analyzes how indigenous populations are socially represented in the curricula of Colombia, Chile, and Ecuador. Methodology. This study employed qualitative research to critically examined curricula of Colombia, Chile, and Ecuador. The categorical analysis focused on evaluating representation of indigenous people as social subjects and their identity. The selected analysis corpus is justified as it explicitly outlines the curricular objectives to be developed within the levels of compulsory school education and makes explicit the skills, attitudes, and levels of achievement throughout the compulsory education cycle. Results. The analysis reveals inconsistencies in the programmatic configuration, the stated pluralistic and intercultural purposes are not concretely addressed but are instead treated as thelos to reach. This situation prevents valorizing the indigenous subjects as active participants in sociohistorical dynamics. Conclusion. Transforming curricula must necessarily begin with developing acts of social and individual reflexivity regarding the objectives, indicators, and didactic strategies implemented in intercultural classrooms, as well as their alignment with the stated principles.